Evaluasi Kebijakan Sistem Zonasi dalam Penerimaan Peserta Didik Baru (PPDB) di Sekolah Menengah Pertama Negeri (SMPN) 1 Abiansemal - I Kadek Dede Junaedy; I Made Mardika; I Made Yudhiantara (Public Inspiration : Jurnal Administrasi Publik, 2021)
Evaluation of the Zoning System Policy in the Admission of New Students (PPDB) at State Junior High School (SMPN) 1 AbiansemalThe zoning system policy in its implementation at SMPN 1 Abiansemal has problems, web is difficult to open during the school selection process by students and since the implementation of the school zoning system it has been difficult to find students who have different academic achievements from when admitting students through the TPA route. This shows that it is necessary to evaluate the zoning system policy. The purpose of this study was to evaluate the zoning system policy in the Admission of New Students at SMPN 1 Abiansemal in terms of equal access and quality of education, as well as to find supporting factors and obstacles to the implementation of zoning system policies at SMPN 1 Abiansemal.The research method used is qualitative research methods. The results showed that the zoning system policy was not implemented effectively and efficiently. And it has not been able to create equal access and equal quality in the Admission of New Students at SMPN 1 Abiansemal, because the zoning has not been carried out evenly and there has been a decline in the quality of schools. Supporting factors of the implementation of the zoning system policy in the Admission of New Students at SMPN 1 Abiansemal, including coordination of the office and the school principal, and having SOPs and technical guidelines for implementing zoning system policies in new student admissions at SMPN 1 Abiansemal. The inhibiting factors for the implementation of the Zoning system policy at SMPN 1 Abiansemal include lack of facilities and infrastructure, lack of human resources, limiting the number of quotas and zoning based on the address of the banjar, and pressure from school external parties.